Internal Factors Associated with the Tendency of Lesbians in Women's Correctional Institutions in Bandar Lampung in 2024 - Nadya Salsabilla; Wayan Aryawati; Nurul Aryastuti; Anita Bustami; Octa Reni Setiawati (Jurnal Ners, 2025)
Lesbianism refers to women who are physically, emotionally, spiritually, and sexually attracted to other women. Indonesia ranks as the fifth-largest country in the world contributing to the spread of LGBT (lesbian, gay, bisexual, and transgender) populations, following China, India, Europe, and America. Independent survey institutions, both domestic and international, estimate that 3% of Indonesia's total population identifies as LGBT. This equates to approximately 7.5 million individuals, meaning that in a gathering of 100 people, around three may be LGBT. This phenomenon is also observed in confined environments such as women's correctional institutions, where internal factors may influence the tendency toward lesbianism. This study aims to analyze internal factors associated with the tendency toward lesbianism in the Class IIA Way Hui Women's Correctional Institution in Bandar Lampung. This research employs a descriptive-analytical approach with a cross-sectional study design. The population consists of 182 female inmates, selected using a total sampling technique. Data were collected through a questionnaire and analyzed using univariate (frequency distribution), bivariate (chi-square test), and multivariate (multiple logistic regression) analyses. Results The study found that 36 respondents (19.8%) exhibited a tendency toward lesbianism. Psychological problems were reported by 37 respondents (20.3%), while 145 (79.7%) did not experience such issues. Additionally, 74 respondents (40.7%) had biological factors contributing to their behavior, whereas 108 (59.3%) did not. Educational background also played a role, with 102 respondents (56.0%) having lower education levels and 80 (45.5%) having higher education. Furthermore, 77 respondents (42.3%) had experienced traumatic or negative past events, while 105 (57.7%) had not. Age was also analyzed, with 117 respondents (64.3%) considered at-risk and 65 (35.7%) not at-risk. Statistical analysis revealed significant associations between lesbian tendencies and physical factors (p-value = 0.000), psychological factors (p-value = 0.026), past experiences (p-value = 0.000), and education (p-value = 0.000). However, no significant relationship was found between age and lesbian tendencies (p-value = 0.091). The most dominant influencing factor was physical factors (p-value = 0.003, OR = 4.010). Conclusion Internal factors, particularly physical and psychological aspects, play a dominant role in the tendency toward lesbianism in correctional institutions. Therefore, it is recommended that the Bandar Lampung Women's Correctional Institution enhance educational, counseling, religious, and therapy programs focusing on prevention and psychological well-being.